2020
DOI: 10.1371/journal.pgen.1008718
|View full text |Cite
|
Sign up to set email alerts
|

Novel loci for childhood body mass index and shared heritability with adult cardiometabolic traits

Abstract: Sanofi Aventis, Servier & Takeda. MS receives funding from Pfizer Inc. for a project not related to this research. IB and spouse own stock in GlaxoSmithKline and Incyte Corp. ZE and CDB currently serve on the editorial board of PLOS Genetics. AC reports personal fees from Novartis, personal fees from Thermo Fisher Scientific, personal fees from Philips, personal fees from Sanofi, personal fees from Stallergenes Greer, outside the submitted work. KC in involved in consultancy for Danone Research, LNC-therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 76 publications
(140 reference statements)
7
111
0
1
Order By: Relevance
“…As reviewed by others, 27,28 genome-wide association studies (GWAS) have been effective in the identification of more than 1,000 genetic loci associated with adiposity-related outcomes, such as adult BMI, 29 body fat percentage, 30 and obesity as a binary trait, 31 and child BMI-standard deviation score 32 and obesity. 33 The vast majority of these loci were identified for adult BMI (N = 941 loci, explaining 6% of adult BMI variance 29 ).…”
Section: Genetic Determinants Of Physical Activity Sedentary Behaviour and Adiposity-related Traitsmentioning
confidence: 99%
“…As reviewed by others, 27,28 genome-wide association studies (GWAS) have been effective in the identification of more than 1,000 genetic loci associated with adiposity-related outcomes, such as adult BMI, 29 body fat percentage, 30 and obesity as a binary trait, 31 and child BMI-standard deviation score 32 and obesity. 33 The vast majority of these loci were identified for adult BMI (N = 941 loci, explaining 6% of adult BMI variance 29 ).…”
Section: Genetic Determinants Of Physical Activity Sedentary Behaviour and Adiposity-related Traitsmentioning
confidence: 99%
“…This study was limited, in that there were far fewer childhood BMI SNPs (N = 14 and 5) than adult BMI SNPs (N = 323 and 115), decreasing the power of the MR estimation (Au Yeung et al, 2021). Our twosample MR using 25 childhood BMI SNPs (Vogelezang et al, 2020) supports a causal relationship with asthma. However, based on the previous study (Au Yeung et al, 2021) and our result, childhood BMI has a weak causal impact on asthma but not on any specific subtype.…”
Section: Discussionmentioning
confidence: 71%
“…To determine the effect of childhood BMI on asthma in our setting, we extracted 25 childhood BMI SNPs with associated statistical values from a previous study ( Vogelezang et al, 2020 ). These BMI SNPs were subject to the removal of SNPs with strand ambiguity (e.g., A/T and C/G), SNPs in the MHC region (chromosome 6:25-34M), SNPs with no proxy ( r 2 > 0.8) in UKB, and SNPs that were associated with asthma ( P < 2.17E–03, 0.05/23) leaving 21 SNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a multi-ethnic GWAS in adults has found an association between rs1650505 (near EBF1 ) and pericardial adipose tissue volume 56 . Previous studies found substantial overlaps between childhood and adult obesity GWAS loci 62 . While there is relatively weak LD between the lead SNP showing pleiotropic effect in our study (rs6887211) and rs1650505 (r 2 = 0.06 in CEU), we acknowledge that the novelty of the locus in childhood BMI may be in part due to the small study power of the source GWAS used for childhood BMI.…”
Section: Discussionmentioning
confidence: 95%